Numerical estimates of the accretion rate on to intermediate-mass black holes - Pepe, Carolina (2013)
The existence of intermediate-mass (∼103 M⊙) black holes (IMBHs) in the centre of glob- ular clusters has been suggested by different observations. The X-ray sources observed in NGC 6388 and in G1 in M31 could be interpreted as being powered by the accretion of matter on to such objects. In this work, we explore a scenario in which the black hole accretes from the cluster interstellar medium, which is generated by the mass-loss of the red giants in the cluster. We estimate the accretion rate on to the black hole and compare it to the values obtained via the traditional Bondi–Hoyle model. Our results show that the accretion rate is no longer solely defined by the black hole mass and the ambient parameters but also by the host cluster itself. Furthermore, we find that the more massive globular clusters with large stellar velocity dispersion are the best candidates in which accretion on to IMBHs could be detected.